Culture and memory in medieval Islam essays in honour of Wilferd Madelung - Daftary, Farhad 1938-; Meri, Josef W. 1969- (I.B. Tauris, 2003)
The relationship between the workings of memory and the formation of culture is intriguingly close in the world of medieval Islam. In this book, distinguished contributors explore broad-ranging themes relating to memory, memorisation, memorialising or commemorating in a variety of historical, legal, literary and architectural contexts. Abbas Amanat, Irene Bierman, Elton Daniel, George Makdisi, Andrew Newman, Roy Mottahedeh, Ismail K. Poonawala and Paul E. Walker examine lists and maps as memory aids, the transmission of knowledge and traditions from medieval to early-modern times, the applicat